Risk factors for acute chest syndrome among children with sickle cell anemia hospitalized for vaso-occlusive crises - Faisal A. Alghamdi; Fawaz Al-Kasim; Forat Alshhada; Eatedal Ghareeb; Fauzia R. Azmet; Adel Almudaibigh; Lobna Baitalmal; Bedah Alnawfal; Rehab Alluqmani (Scientific Reports, 2024)
Abstract Sickle cell anemia (SCA) is a globally prevalent inherited condition, with acute chest syndrome (ACS) being one of its most severe complications. ACS frequently leads to hospitalization, requires intensive care unit (ICU) admission, and can even result in death. This study aimed to discern the early indicators of impending ACS in children with SCA who were initially hospitalized due to painful vaso-occlusive crises (VOC). This was a retrospective, case‒control investigation of 120 patients aged 1–14 years seen at the King Saud Medical City in Riyadh, Saudi Arabia from January 2021 to December 2022. Patients were classified into cases and controls: those who developed and did not develop ACS during hospital stay, respectively. Demographic factors, laboratory results, vital and clinical signs, and treatment protocols were compared between these groups. The following were significant predictors of impending ACS: previous diagnosis of asthma, history of ACS, recent upper respiratory tract symptoms prior to admission, and need for a blood transfusion within the first 24 h of admission due to a drop in hemoglobin levels. Further regression analysis indicated that elevated steady-state mean corpuscular volume, leukocyte count, total bilirubin, and an increased absolute neutrophil count level 24 h after admission also foreshadowed impending ACS among patients admitted for VOC. The location of pain was also significant; the incidence of ACS was higher in patients with back pain, but lower in those with pain confined to the limbs. The ACS group had a longer average duration of hospital stay compared to those with VOC alone, (7.6 vs. 5.8 days). Among patients initially admitted for VOC, 15.7% were diagnosed with ACS. Most ACS cases were managed with transfusions and antibiotics, and nearly one-third of patients needed admission to an ICU or a high-dependency area.